Analysis of COVID-19 Patients With Acute Respiratory Distress Syndrome Managed With Extracorporeal Membrane Oxygenation at US Academic Centers. Issue 1 (July 2021) - Nguyen, Ninh T.; Sullivan, Brittany; Sagebin, Fabio; Hohmann, Samuel F.; Amin, Alpesh; Nahmias, Jeffry
Abstract : Objective: This study analyzed the outcomes of COVID-19 patients with ARDS who were managed with extracorporeal membrane oxygenation (ECMO) across 155 US academic centers. Summary Background Data: ECMO has been utilized in COVID-19 patients with acute respiratory distress syndrome (ARDS) and refractory hypoxemia. Early case series with the use of ECMO in these patients reported high mortality exceeding 90%. Methods: Using ICD-10 codes, data of patients with COVID-19 with ARDS, managed with ECMO between April and September 2020, were analyzed using the Vizient clinical database. Outcomes measured included in-hospital mortality, hospital and ICU length of stay, and direct cost. For comparative purposes, the outcome of a subset of COVID-19 patients aged between 18 and 64 years and managed with versus without ECMO were examined. Results: 1, 182 patients with COVID-19 and ARDS received ECMO. In-hospital mortality was 45.9%, mean length of stay was 36.8 ± 24.9 days, and mean ICU stay was 29.1 ± 17.3 days. In-hospital mortality according to age group was 25.2% for 1 to 30 years; 42.2% for 31 to 50 years; 53.2% for 51 to 64 years; and 73.7% for ≥65 years. A subset analysis of COVID-19 patients, aged 18 to 64 years with ARDS requiring mechanical ventilation and managed with (n = 1113) vs without (n = 16, 343) ECMO, showed relatively high in-hospital mortality for both groups (44.6% with ECMO vs 37.9% without ECMO). Conclusions: In this large US study of patients with COVID-19 and ARDS managed with ECMO, the in-hospital mortality is high but much lower than initial reports. Future research is needed to evaluate which patients with COVID-19 and ARDS would benefit from ECMO.